Proceedings of the 44th IEEE Conference on Decision and Control
DOI: 10.1109/cdc.2005.1582260
|View full text |Cite
|
Sign up to set email alerts
|

State Representations From Finite Time Series

Abstract: We present two algorithms for construction of a state sequence of a linear time-invariant system from a finite exact trajectory of that system. The first algorithm uses the classical in subspace identification splitting of the data into "past" and "future" and computes a bases for the past-future intersection. The second algorithm, based on the shift-and-cut map, operates on a half deeper Hankel matrix.Index Terms-Subspace identification, state construction, shift-and-cut map, persistency of excitation, behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This is the key property that enables one to replace a parametric description of the system with data. Lemma 2 has been originally proven in [27, Theorem 1] using the behavioral language, and it was later referred to in [33] as the fundamental lemma to describe a linear system through a finite collection of its input/output data. Here, for making the paper as self-contained as possible, we gave a proof of this result using state-space descriptions, as they will recur often in the reminder of this paper.…”
Section: A Persistently Exciting Data and The Fundamental Lemmamentioning
confidence: 99%
“…This is the key property that enables one to replace a parametric description of the system with data. Lemma 2 has been originally proven in [27, Theorem 1] using the behavioral language, and it was later referred to in [33] as the fundamental lemma to describe a linear system through a finite collection of its input/output data. Here, for making the paper as self-contained as possible, we gave a proof of this result using state-space descriptions, as they will recur often in the reminder of this paper.…”
Section: A Persistently Exciting Data and The Fundamental Lemmamentioning
confidence: 99%
“…Therefore, our remaining task is to computeȳ [0,4] . Inspired by [2], we will compute this trajectory iteratively by computing multiple length 3 trajectories as linear combinations of the columns of (16). To begin with, we compute the first unknown in (18), which isȳ(0).…”
Section: A Identification With Missing Data Samplesmentioning
confidence: 99%
“…In the seminal work by Willems and coauthors [1], it was shown that a single, sufficiently exciting trajectory of a linear system can be used to parameterize all trajectories that the system can produce. This result has later been named the fundamental lemma [2], [3], and plays an important role in the learning and control of dynamical systems on the basis of measured data.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, condition (3) makes it possible to represent any input/output trajectory of the system as a linear combination of previously collected input/output data. Lemma 2 has been originally proven in [22, Theorem 1] using the behavioral language, and it was later referred to as the fundamental lemma [28] to describe a linear system through a finite collection of its input/output data.…”
Section: Preliminaries and The Willems Et Al's Fundamental Lemmamentioning
confidence: 99%